Populism, Radical Democracy, and the Indonesian Process of Democratization - Madung, Otto Gusti Ndegong; Mai, Adrianus Yohanes (Politika: Jurnal Ilmu Politik, 2022)
This paper discusses the ideas of populism as highlighted by Mouffe and Laclau to analyze its relevance for Indonesian democracy context. Populism is a political style which is a source for change based on the systematic use of rhetorical appeal to the people. This research focuses on populism in relation to democracy which brings forth left and right-wing populism. The concept of populism in general leads us to look at the fact of populism in Indonesia democracy context. Some crisis such us economic crisis, poverty, inequality and the failure of the government in looking after the common will and the common good of people lead to create a ‘populist moment’ particularly in Indonesia context. Therefore, radical democracy and left populism of Chantal Mouffe and Ernesto Laclau which this research is focusing on, offers some relevant suggestions to enhance the democratic participation of the people to overcome some crises in Indonesia democracy, which is mostly being co-opted by predatory oligarchy.